Higher education in crisis again: Encroached by authoritarianism, unfreedom and violence - Waghid, Yusef (South African Journal of Higher Education, 2025)
Higher education globally is once again at a crossroads, increasingly threatened by authoritarianism, repression, and violence. In this article, I examine how universities – historically sites of critical inquiry, deliberation, and democratic engagement – are being targeted by authoritarian regimes and subjected to escalating constraints on academic freedom. Drawing on global examples from Hungary, Turkey, India, Brazil, and the United States, I accentuate a disturbing pattern: governments seeking to silence dissent view universities as threats, attacking scholars, students, and institutional autonomy. These intrusions are not limited to authoritarian states; even established democracies have shown intolerance toward critical scholarship and campus activism. In the African context, the struggle for academic freedom is deeply rooted in histories of colonial repression and postcolonial authoritarianism. South Africa, despite its constitutional protection of academic freedom, has experienced violent state responses to student movements like #FeesMustFall, revealing ongoing tensions between democratic ideals and coercive state practices. Across the continent, universities remain both symbols of resistance and vulnerable sites of state control. I posit that the university’s core values – freedom, deliberation, and justice – are indispensable for democratic life. My contention is that higher education must foster critical, ethical citizens committed to the public good. Drawing on the African philosophical tradition of ubuntu, I once again advocate for an education that promotes human dignity, interconnectedness, and justice. In the main, the article is a call to resist authoritarian encroachment and reaffirm the university’s democratic mission. By defending academic freedom and creating spaces for inclusive deliberation, universities can buttress tyrannical action and contribute more plausibly to a more just society.